2020
DOI: 10.1177/0885328220972219
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic bone-like composites as osteo-odonto-keratoprosthesis skirt substitutes

Abstract: Osteo-odonto-keratoprostheses, incorporating dental laminate material as an anchoring skirt around a central poly(methyl methacrylate) (PMMA) optic, have been used to replace the cornea for many years. However, there are many intricacies associated with the use of autologous dental laminate material, surgical complexity and skirt erosion. Tissue engineering approaches to bone replacement may offer suitable alternatives in osteo-odonto-keratoprosthesis (OOKP) surgery. In this study, a hydrogel polymer composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…They also added poly(ethylene glycol) diacrylate (PEGDA) polymers and agarose to improve the mechanical strength of the hydrogels. This study suggested the PEGDA-agarose based IPN can be used in the future to replace the OOKP lamina ( 89 ).…”
Section: Hard Keratoprosthesesmentioning
confidence: 97%
See 1 more Smart Citation
“…They also added poly(ethylene glycol) diacrylate (PEGDA) polymers and agarose to improve the mechanical strength of the hydrogels. This study suggested the PEGDA-agarose based IPN can be used in the future to replace the OOKP lamina ( 89 ).…”
Section: Hard Keratoprosthesesmentioning
confidence: 97%
“…To decrease laminar resorption, and simplify the surgical procedure, decrease costs, and avoid oral trauma, skirts made of synthetic materials similar to the osteo-odonto-acrylic lamina have been introduced. Avadhanam et al incorporated nano-crystalline hydroxyapatite (nHAp) coated poly (lactic-co-glycolic acid) PLGA microspheres with a high strength interpenetrating network (IPN) hydrogel to mimic the odonto-acrylic lamina microenvironment ( 89 ). They also added poly(ethylene glycol) diacrylate (PEGDA) polymers and agarose to improve the mechanical strength of the hydrogels.…”
Section: Hard Keratoprosthesesmentioning
confidence: 99%
“…Utilizing a mineralized microenvironment is another strategy that needs further research since the osteoblastic cells could recognize hydroxyapatite as their own substance which helps in increasing cell attachment, proliferation, and differentiation [75,76]. Hydroxyapatite would stimulate the cells to adhere [76], while the modified hydrogels would have an enhanced loading efficiency for DEX.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Other than drug delivery, the scientific community has also reported widespread applications of interpenetrating polymer networks as wound dressing formulations [ 4 6 ], for tissue engineering to design artificial scaffolds [ 7 , 8 ] and injectable supports [ 9 ] and bone graft substitutes [ 10 ], etc. Incorporating natural and/or biopolymers even of synthetic origin is believed to offer a sustainable approach to IPN synthesis owing to the low toxicity profiles of such polymer subunits.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ]. Irradiation with high-energy gamma ( gamma ) and beta ( beta ) rays is recommended for polymer networks because it increases the mechanical stability of the polymers [ 10 ].…”
Section: Introductionmentioning
confidence: 99%